Spinal Space Occupying Lesions: A Comprehensive Study of Clinico-pathological Spectrum and Measure of Degree of Agreement Between the Diagnostic Modalities: Clinico-pathological spectrum of Spinal Space Occupying Lesions (SOLs) - Gubbala, Srinivas DD; Mattaparti, Sridevi; ., Bhavani (Annals of Pathology and Laboratory Medicine, 2020)
Back ground: Spinal SOLs are quite fascinating group of lesions, comprising a minority of central nervous system lesions often resulting in significant morbidity. There is paucity of comprehensive population-based data of these SOLs in Indian subcontinent. Material and methods: The present study was a retrospective descriptive study conducted at the department of pathology, Kamineni Institute of Medical Sciences for 3 years starting from January 2017 to December 2019. Results: We analyzed eighty-nine spinal SOLs during the study period. Spinal neoplasms encompassed the largest number accounting for 70.7% of total spinal SOLs. Majority were reported in the 20-40 years’ age group with predominant male preponderance except for universal phenomenon of female predominance in meningioma. Back pain was the most common clinical presentation. Among spinal neoplasms, NSTs comprising of schwannoma and neurofibroma, was the most common finding and spinal tuberculosis was the most common non-neoplastic SOL. Majority of benign spinal tumors were distributed in the intradural extra medullary location and involved thoracic vertebrae. Malignant tumors predominantly involved extradural location and were clustered along thoracic and lumbar vertebrae. Measure of agreement between radiological and histopathological diagnosis using kappa statistics revealed almost perfect agreement for extradural spinal SOLs and moderate agreement for intradural intramedullary and intradural extra medullary SOLs. Conclusion: Comprehensive evaluation of spinal SOLs warrants multidisciplinary approach. Rapid advancements in radiology optimised diagnostic evaluation of non-neoplastic SOLs, however we conclude that histopathological evaluation is still the gold standard for diagnosis of primary spinal cord tumours and for planning the treatment and predicting prognosis.